A Novel Aerosol Foam Formulation of Calcipotriol and Betamethasone Has No Impact on HPA Axis and Calcium Homeostasis in Patients With Extensive Psoriasis Vulgaris. Issue 1 (January 2016) - Taraska, Victoria; Tuppal, Raj; Olesen, Martin; Bang Pedersen, Claus; Papp, Kim
Background: Fixed combination calcipotriol 50 µg/g (Cal; as hydrate) plus betamethasone 0.5 mg/g (as dipropionate; BD) has been formulated in an innovative aerosol foam. Objective: To assess systemic safety of Cal/BD aerosol foam. Methods: In a multicentre, single-arm, open-label, maximal-use systemic-exposure trial, adult patients with moderate to severe, extensive psoriasis (15%-30% of body surface area, including ≥30% of scalp) applied Cal/BD foam once daily. Endpoints were week 4 abnormal adrenocorticotropic hormone (ACTH) challenge test and change in albumin-corrected serum calcium, 24-hour urinary calcium excretion, and urinary calcium-creatinine ratio. Results: 35 patients reaching week 4 exhibited normal ACTH responses. At week 4, changes in calcium homeostasis were minor and not clinically relevant; no patients experienced elevations above normal. Disease severity generally improved, and 49% of patients achieved treatment success according to the Physician's Global Assessment of Disease Severity. Conclusion: No clinically relevant HPA axis or calcium homeostasis impact was observed with 4 weeks of once-daily Cal/BD foam in patients with extensive psoriasis vulgaris.